Long-term survival of enamel-defect-affected teeth - Hong, Chuen Lin (Caries Res, 2020)
There has been considerable research focussed on the occurrence and aetiology of developmental defects of enamel, but less is known about the extent to which enamel-defect-affected teeth may be at greater risk for dental caries. The Dunedin Multidisciplinary Health and Development Study is a prospective cohort study of 1,037 children born in Dunedin, New Zealand between 1 April 1972 and 31 March 1973. Participants were examined for the presence of developmental defects of enamel at age 9 years and then repeatedly for the occurrence of dental caries through to age 45 years. After controlling for confounding variables, incisor teeth affected by demarcated opacities at age 9 were 3.4 times more likely to be restored than teeth unaffected by defects. Incisors with diffuse opacities and hypoplasia or combinations of defects were 2.8 times more likely to be restored. Molars with enamel defects of any type did not have significantly different risk for being subsequently restored or lost due to caries than unaffected molars, except those affected by diffuse opacities, which were at 0.4 times the risk of being lost due to caries. Dental clinicians should be aware that enamel-defect-affected teeth are not necessarily at greater risk for tooth loss due to caries in the long term, but permanent incisors affected by enamel defects are at higher risk of receiving restorative intervention.